Efficacy and safety of switching to dolutegravir plus emtricitabine/tenofovir disoproxil fumarate (TDF) or elvitegravir/cobicistat/emtricitabine/TDF in virologically suppressed HIV‐infected patients in clinical practice: results from a multicentre, observational study. Issue 2 (20th November 2018) - Baldin, G; Ciccullo, A; Capetti, A; Rusconi, S; Sterrantino, G; Cossu, MV; Giacomelli, A; Lagi, F; Latini, A; Bagella, P; De Luca, A; Di Giambenedetto, S; et al.
Abstract : Objectives: The aim of the study was to compare the efficacy and tolerability of switching antiretroviral therapy to dolutegravir + emtricitabine/tenofovir disoproxil fumarate (TDF) with those of switching to elvitegravir/cobicistat/emtricitabine/TDF in clinical practice. Methods: In a multicentre real‐life observational study, we analysed data for HIV‐infected patients on antiretroviral treatment with viral load < 50 HIV‐1 RNA copies/mL switching to dolutegravir + emtricitabine/TDF (dolutegravir group) or elvitegravir/cobicistat/emtricitabine/TDF (elvitegravir group). Follow‐up was censored at 48 weeks. Results: The 48‐week estimated proportion maintaining virological efficacy was 96.1% with dolutegravir ( n = 123) and 95.4% with elvitegravir ( n = 186; P = 0.941). Patients in the dolutegravir group showed more treatment discontinuations, but these were mainly as a result of simplification. The elvitegravir group showed more discontinuations because of renal adverse events (2.7% versus 0% with dolutegravir). Interestingly, no difference was observed between the two regimens in central nervous system toxicity‐related discontinuations. Switching to dolutegravir was associated with a better blood lipid profile. Conclusions: Switching to dolutegravir + emtricitabine/TDF was associated with similar efficacy and tolerability to switching to elvitegravir/cobicistat/emtricitabine/TDF in virologically suppressed patients in clinical practice, although reasons for discontinuation showed differences between regimens. These results should be interpreted with caution, as this is a nonrandomized comparison.